Drivers of Change: Youth Action in Lempangang Village, Gowa Regency, South Sulawesi in the Service of Pancasila Village - Nurhikmah; Musaldin, La Ode; Purnamasari, Nur Indah (LPPM STAI Darul Falah, 2024)
The purpose of this article is a form of dedication to the Pancasila village in Boto Lempangang to strengthen the sense of unity among the community but also to make a real contribution to improving the quality of life of the village residents. Activities such as social service, education, skills training, and environmental initiatives are a means of implementing Pancasila values in everyday life. Their work has become an inspiration for other villages to work together to maintain and develop the values that are the identity of the Indonesian nation. This research uses qualitative research using a case study design. Data collection techniques include interviews, observations, and documentation. Data analysis techniques include data reduction, presentation, conclusion drawing, and verification stages. The research results show that the initiative carried out by the youth of Lempangang Village in the Kampung Pancasila program has had a significant positive impact on the local community. Through various programs such as agricultural counseling, national education and healthy living, developing MSMEs, and increasing food security, village youth have succeeded in strengthening local capacity and creating sustainable change. These programs not only improve economic welfare and public health but also strengthen national values and social solidarity.